Model Aplikasi Manajemen Kehadiran Pegawai Menggunakan Lokasi dan Kamera Real-Time Berbasis Feature Modelling - Saputra W, Inyoman; Noprisson, Handrie (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
One aspect that attracts attention to employee development is in terms of attendance management in the company. Attendance management holds significant importance in many areas. In personnel management, attendance is very important for salary calculation and increases concern for job responsibilities. This research will use waterfall methodology involving sequential phases such as needs analysis, system design, implementation, testing, and maintenance using modeling that is different from previous research, namely using feature modeling. The main features used are face and location recording includes the utilization of camera technology and location detection as the features are better compared to manual recording. IPresent application testing using blackbox method. One of the tests is testing the main attendance feature, namely recording attendance without granting location access permission. The result of this test is an attendance recording system so that employees cannot record entry or exit. Another test is when employees are out of reach of the office. The result of this test is that the system refuses attendance recording because it is outside a predetermined radius so that employees cannot record attendance.